Open and Percutaneous Approaches Have Similar Biomechanical Results for Primary Midsubstance Achilles Tendon Repair: A Meta-analysis - Jonathan Lawson, M.S; Rae Tarapore, M.D; Sean Sequeira, M.D; Casey Imbergamo, M.D; Mitchell Tarka, M.D; Gregory Guyton, M.D; Walter Hembree, M.D; Heath Gould, M.D (Elsevier, 2024)
Purpose: To evaluate the biomechanical properties of open versus percutaneous Achilles tendon repair. Methods: A systematic review of original research articles was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. To qualify for study inclusion, articles were required to be published in English, use a laboratory design using either human or animal tissue, and directly compare the biomechanical properties of open Achilles repair using a Krackow or Kessler technique with percutaneous repair using either a locking or nonlocking suture construct. The biomechanical outcomes evaluated were displacement (millimeters) and load to failure (Newtons). Results: Twelve studies met inclusion criteria, including 234 specimens (open: 97, percutaneous locking: 73; percutaneous nonlocking: 64) that underwent primary midsubstance Achilles tendon repair. Pooled analysis demonstrated no statistically significant difference in displacement (P = .240) or load to failure (P = .912) between the open and percutaneous techniques. Among the percutaneous approaches, there was no difference in displacement (P = .109) between the locking and nonlocking tendon repair systems. Conclusions: The results of this study suggest that both open and percutaneous techniques are biomechanically viable approaches for primary midsubstance Achilles tendon repair. Clinical Relevance: In clinical studies, similar rerupture rates have been observed after open or percutaneous Achilles tendon repair. It may be beneficial for surgeons to understand whether biomechanical differences exist between these repair techniques.